Відображення постаті Богдана Хмельницького у сучасній польській історіографії - Ткачук, А.І. (Історичний архів. Наукові студії, 2014)
Досліджено основні погляди сучасної польської історіографії стосовно особистості
гетьмана Богдана Хмельницького та визвольної війни українського народу. Відзначено,
що значним здобутком істориків Польщі став вихід монографії Я. Качмарчека. Разом із
тим, численність публікацій у порівнянні з попередніми періодами не є надто великою.
Польські історики визначилися із термінологією при висвітленні подій середини ХVI століття. Исследовано основные взгляды современной польской историографии относительно
личности Богдана Хмельницкого и освободительной войны украинского народа.
Отмечено, что значительным достижением историков Польши стала публикация
монографии Я. Качмарчека. Вместе с тем, численность публикаций в сравнении с
предыдущими периодами не есть слишком большой. Польские историки определились
из терминологией при изложении событий средины ХVI века. Basic provisions of modern Polish historiography according getman Bohdan Khmelnytsky’s
personality and liberating war of the Ukrainian people are investigated. It’s found out that
considerable achievement of historians there was the release of monography of Y. Kacmarcik.
At the same time, the number of publications is comparison with the previous period isn’t too
large. The polish historians decided on terminology by consideration of the middle of the 16th
century. It is characteristic that along with historians the important place to reseach of these
events was taken also by philologists. They tried to estimate better acts of a getman through the
novel by Henryk Sienkiewicz's novel "Fire and sword" prism.